Classification and analysis of nutrition and health claims on Indian packaged food products - Vartika Chaudhary; Dinesh Sharma (CyTA - Journal of Food)
Nutrition and health (NH) claims are extensively used on food packages to convey health benefits of food products to consumers in India. However, Indian regulatory guidelines do not provide a detailed classification of NH claims. Hence, first comprehensive NH claim sub-types are identified by studying regulatory guidelines of various countries as well as the academic literature. Next, 1123 claims on 112 health-based packaged food products from India are analysed based on typologies identified. The results reveal a high occurrence of NH claims. Within NH claims, there was a higher presence of nutrition claims over health claims; components to encourage over limit; and non-numeric over numeric claims. Moreover, claim types that are popular in the market but have received limited research attention, such as numeric, non-addition, nutrient comparative, component to limit, and implied claims, are highlighted. This work can help Indian policymakers to re-evaluate and revise current claim guidelines.